Designing outdoor environments for children landscaping schoolyards, gardens, and playgrounds - Tai, Lolly (New York McGraw-Hill, 2006)
This unique resource expertly details the design, installation, and maintenance of sustainable children's landscapes and play yards. Numerous case studies cover projects including storybook courtyards, music and barnyard gardens, nature trails, wildlife habitats, memorial, and edible gardens.
History and development -- The design process -- Children's gardens -- Schoolyards, playgrounds, and backyards -- Sustainable landscape concepts -- Curriculum, fund raising and community partnerships, and service learning.
Keywords: Playgrounds -- Design and construction; Play environments -- Design and construction